2017
DOI: 10.1007/s00415-017-8646-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of cortical superficial siderosis in patients with acute stroke

Abstract: Cortical superficial siderosis (cSS) is a pathologic and radiologic diagnosis of hemosiderin deposition in subpial brain layers. However, cSS has not been fully studied in patients with acute stroke. Here, we investigated the prevalence of cSS in patients with acute stroke and analyzed the relationship between cSS and different clinical and neuroimaging characteristics. From September 2014 through June 2016, consecutive patients with acute stroke who were admitted to our department were retrospectively investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…cSS may be identified in 1% of patients with acute ischemic stroke. 34 cSS is associated with a high risk of subsequent intracerebral hemorrhage and is considered a highly specific finding of CAA. 14,15 We found cSS in 3% of our patients but only 4 had a disseminated cSS, the subtype with the highest risk of intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…cSS may be identified in 1% of patients with acute ischemic stroke. 34 cSS is associated with a high risk of subsequent intracerebral hemorrhage and is considered a highly specific finding of CAA. 14,15 We found cSS in 3% of our patients but only 4 had a disseminated cSS, the subtype with the highest risk of intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…23 Compared with CMBs, cSS is rare in the normal population. For example, in the population-based Rotterdam Scan Study, only 0.7% of the elderly populations had cSS; 31 in a Japanese cohort study, which evaluated the prevalence of cSS in acute stroke, 32 cSS was found in 1.0% of patients with ischemic 23 and SAH and subarachnoid extension of ICH underlie cSS. Notably, we found that hemorrhagic transformation after ischemic stroke accounted for approximately half of the cSS cases.…”
Section: Discussionmentioning
confidence: 99%
“…High brain natriuretic peptide (BNP) or N-terminal pro B-type natriuretic peptide (NT-proBNP) levels were defined as >100 or >300 pg/mL, respectively ( 25 , 26 ). Gradient-recalled echo T2*-weighted images were assessed for evidence of cerebral microbleeds (CMBs), defined as parenchymal hemorrhage ≤10 mm in diameter ( 27 ). Stroke severity on admission and on discharge was assessed using the National Institutes of Health Stroke Scale (NIHSS) score and the mRS score, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Gradient-recalled echo T2*-weighted images were assessed for evidence of cerebral microbleeds (CMBs), defined as parenchymal hemorrhage ! 10 mm in diameter (27). Stroke severity on admission and on discharge was assessed using the National Institutes of Health Stroke Scale (NIHSS) score and the mRS score, respectively.…”
Section: Clinical Characteristicsmentioning
confidence: 99%